A comparative analysis of online alternative & mainstream newspapers in Malaysia & Pakistan during the 2018 general election - Asad, Saira (2021)
The study discovered the representational roles of social actors (Dr. Mahathir, Najib Razak, Imran Khan & Nawaz Sharif) in alternative and mainstream newspapers (Malaysiakini, The New Straits Times, Dawn & The News) of Malaysia and Pakistan in 2018 elections’ campaigns. The varied representation of social actors showed an ideological inclination of newspapers. Critical Discourse Analysis (CDA) of Fairclough’s (1995) serves to discover the political developments of contexts in both countries. Social actors’ representation in news reports led to differentiation of their roles through activation and passivation. It was analyzed by employing van Leeuwen’s (2005) socio-semiotic analysis. Halliday’s (1978, 1985) framework of Systemic Functional Linguistics (SFL) also fulfills the aim of the study in disclosing the power relations among the social actors, newspapers and news reports. Halliday and Matthiessen’s (2014) analytical tool of ‘Transitivity’ analyzed the social actors’ role in processes and participants that differentiate their representation in both streams of newspapers, while interpersonal realization was analyzed through Martin and White’s (2005) ‘Attitude’ analysis. The hard news reports from online newspapers were selected on the issue of ‘corruption’. The news reports were selected from April 26th, 2018 to May 23rd, 2018 in Malaysia, and July12th, 2018 to August 7th, 2018 in Pakistan based on two weeks before and two weeks after the elections’ time frames. The study’s main findings showed that Dr. Mahathir and Imran Khan were the most activated social actors. In Malaysia, the social actors presented higher in ‘Material’ and ‘Verbal’ processes, while occupying the participant roles of ‘Verbiage’, ‘Sayer’, and ‘Actor’. In contrast in Pakistan, most occurrences were found in the ‘Verbal’ process in ‘Sayer’ participant role through the Transitivity analysis. Higher interpersonal realization of social actors showed in ‘Judgment’ attitudinal resource in all newspapers. The results revealed that previous governments’ performances in both countries were supported a higher negative presentation of the issue. In Malaysia, issues such as high cost of living, general service tax, corruption, 1Malaysia Development Berhad (1MDB), and shifting loyalties of former Barisan Nasional’s (BN) leaders were influential factors vi that caused BN decline. In Pakistan, military involvement, corruption, and previous government corrupt practices were the main factors of political developments. The social situations (context) found the power dynamics behind the discourse. The findings will contribute in print journalism, communication studies, linguistics, cultural studies, and political science to represent the inclination of newspapers toward a particular social actor by the analysis of transitivity analysis and attitude subsystem used in news reports. This study is a beneficial contribution in literature, where the 2018 elections of Malaysia and Pakistan were not investigated earlier through textual analysis. For future recommendations, further studies are suggested to compare between Asian and Western hard news reporting on similar issues through Transitivity and Appraisal analysis.